Up, up and away: bird‐mediated ectozoochorous dispersal between aquatic environments. (25th January 2017) - Coughlan, Neil E.; Kelly, Thomas C.; Davenport, John; Jansen, Marcel A. K.
Summary: Aquatic birds can facilitate the dispersal of plants, animals, microbes and fungi. Here, we review existing literature on bird‐mediated external (ectozoochorous; synonyms epizoochorous, exozoochorous) dispersal to determine the importance of birds as mobile links between aquatic environments, and to evaluate ectozoochory as a mechanism of dispersal for aquatic organisms and their propagules (collectively referred to as dispersal units). Bird‐mediated ectozoochory occurs when dispersal units stick to feathers, feet and bills, become enmeshed within plumage or encapsulated within mud coating the soft parts of vector birds. The importance of waterbird‐mediated ectozoochorous dispersal relates to the topical problems of increasing anthropogenic habitat fragmentation, climate change and the associated alterations in species distributions and biological invasions. Nevertheless, some aspects of the bird‐mediated ectozoochorous dispersal remain understudied, and poorly understood. This review identifies two areas where further research is required. Firstly, the quantitative contribution of bird‐mediated ectozoochory to overall dispersal remains unclear. Secondly, greater consideration of all the requirements necessary for successful waterbird‐mediated ectozoochorous dispersal is needed. In particular, the impact of factors which influence attachment and detachment of dispersal units (e.g. dispersal unit densities, preening behaviour and the role of encapsulating mud) needs further examination. Moreover, few investigators have taken the step of examining viability of found dispersal units, and fewer still have examined tolerances of dispersal units to the 'in‐flight' conditions experienced during transport, in order to determine probability of survival of external dispersal. Evidence presented in this review indicates that bird‐mediated ectozoochorous transport of aquatic dispersal units is a frequent process, at least at a local scale, and therefore needs to be considered in the context of connectivity and gene flow between isolated aquatic environments.